Red pill, blue pill : how to counteract the conspiracy theories that are killing us - Neiwert, David A., 1956- (Prometheus Books, 2020)
"A revealing trip down the rabbit hole of conspiracy theories-their appeal, who believes them, how they spread-with an eye to helping people deal with the alt-right conspiracists in their own lives. Conspiracy theories are killing us"--